More on the relationship between drawing and project - Chiara Vernizzi; Enrico Prandi (Festival dell'Architettura Magazine, 2022)
Is there still a need to reflect on a classic theme of the disciplinary research of architecture such as the relationship between design and project? We think so, for a few reasons. It is no coincidence that many architects – defined Masters for their suggestion of a way forward in the project – have directly or indirectly expressed an opinion on this crucial theme of architectural research, reaffirming its importance as an irreplaceable tool. But the ultimate reason is the change in the boundary conditions given by the evolution (or involution) of the expressive instrumentation available to the practice of the project. Faced with the danger that CAD will turn from a tool to help drawing into a design tool, it is not superfluous to reiterate on the one hand the fundamentals of the design discipline and on the other the importance of hand drawing.